GSDMD-Mediated Cardiomyocyte Pyroptosis Promotes Myocardial I/R Injury. Issue 3 (23rd July 2021) - Shi, Huairui; Gao, Yang; Dong, Zhen; Yang, Ji'e; Gao, Rifeng; Li, Xiao; Zhang, Shuqi; Ma, Leilei; Sun, Xiaolei; Wang, Zeng; Zhang, Feng; Hu, Kai; et al.
Abstract : Rationale: Pyroptosis is a morphologically and mechanistically distinct form of cell death and is characterized by GSDMD (gasdermin D) or GSDME (gasdermin E)-mediated necrosis with excessive inflammatory factor release. Cardiomyocyte necrosis and inflammation play key roles in the pathophysiology of myocardial ischemia/reperfusion (I/R) injury. However, whether cardiomyocytes undergo pyroptosis and the underlying mechanism in myocardial I/R injury remain unclear. Objective: We aimed to investigate the role of pyroptosis in myocardial I/R injury. Methods and Results: In vivo and in vitro experiments were used to investigate pyroptosis of cardiomyocyte and the associated mechanisms during I/R injury. Wild-type, Myh6-Cre, and cardiomyocyte-specific GSDMD-deficient male mice were subjected to I/R. Human peripheral blood samples were collected from patients with acute ST-segment–elevation myocardial infarction or control patients at 0, 1, and 24 hours after percutaneous coronary intervention in our department. The serum levels of GSDMD were measured by ELISA. Hypoxia/reoxygenation induced cardiomyocyte pyroptosis and the release of mature IL (interleukin)-18 but not IL-1β, which mechanistically resulted from GSDMD cleavage by caspase-11 in cardiomyocytes. Furthermore, GSDMD gene deletion blocked hypoxia/reoxygenation-induced cardiomyocyte pyroptosis and IL-18 release. GSDMD and its pyroptosis-inducing N-terminal fragment were upregulated in myocardial tissues after I/R injury. Immunofluorescence analysis showed that GSDMD was mainly localized in cardiomyocytes. GSDMD deficiency in cardiomyocytes significantly reduced the I/R-induced myocardial infarct size. Moreover, increased GSDMD serum levels were detected in patients exhibiting I/R injury 1 hour after percutaneous coronary intervention for ST-segment–elevation myocardial infarction. Conclusions: Our results show that GSDMD-mediated cardiomyocyte pyroptosis is a key event during myocardial I/R injury and that the caspase-11/GSDMD pathway may be essential to this process. Additionally, GSDMD inhibition significantly reduces cardiomyocyte pyroptosis and I/R-induced myocardial injury. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.